2014
DOI: 10.21831/pep.v18i1.2122
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Evaluasi Program Layanan Pendidikan Anak Usia Dini (Paud)

Abstract: Penelitian ini bertujuan: (1) mengembangkan model evaluasi program layanan PAUD (TK kelompok B) dan (2) menilai keefektifan model yang dikembangkan. Penelitian ini merupakan research and development. Subjek coba adalah guru dan siswa TK kelompok B. Instrumen pengumpul data adalah kuesioner dan lembar observasi. Uji coba dilakukan 3 tahap dengan jumlah subjek meningkat setiap tahapnya. Analisis validitas kuesioner menggunakan exploratory factor analysis dan cofirmatory factor analysis (CFA). Estimasi reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…One of the evaluations of inputs is facilities evaluation, because facilities are one of the aspects that play an important role in ECE service programs. The evaluation results obtained are facilities that have a positive effect on ECE service programs [20]. In addition to the facets of facilities, there are several other aspects that need to be evaluated on the input component including students, educators, education staff, program content, facilities and infrastructure, management, financing [18].…”
Section: Discussionmentioning
confidence: 99%
“…One of the evaluations of inputs is facilities evaluation, because facilities are one of the aspects that play an important role in ECE service programs. The evaluation results obtained are facilities that have a positive effect on ECE service programs [20]. In addition to the facets of facilities, there are several other aspects that need to be evaluated on the input component including students, educators, education staff, program content, facilities and infrastructure, management, financing [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the children will be happy if the teacher gives them enthusiasm in carrying out activities in the classroom such as singing activities. In the opinion of Gunartha, Kartowagiran, & Suardiman, (2014) the responses shown by children when motivated by the teacher are as follows: a) Diligent in facing tasks, b) Tenacious in facing difficulties, c) Shows interest in various people's problems. Based on this opinion, it can be concluded that students will be very enthusiastic, enthusiastic and try to follow and practice when educators provide interesting lessons that have never been done by students.…”
Section: Application Of Audio Media Creative Model For Early Childhoo...mentioning
confidence: 99%
“…Munthe menyatakan bahwa evaluasi tidak hanya berkaitan dengan menilai tetapi melihat faktor berhasil atau tidaknya sebuah progam (Munthe, 2015). Perlunya evaluasi sarana prasarana pada pendidikan TK, karena standar sarana prasarana TK banyak yang tidak sesuai (Gunartha et al, 2014). Pemerintah telah berupaya mengatasi masalah kualitas lembaga PAUD tersebut dengan mengeluarkan Peraturan Menteri Pendidikan Nasional No.…”
Section: Pendahuluanunclassified